2019
DOI: 10.3904/kjim.2017.152
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent reversal of significant intrapulmonary shunt after liver transplantation

Abstract: Repeated CE is useful to evaluate intrapulmonary vascular change before and after LT. Reversal of IPS after successful LT is time-dependent and follow-up duration should be considered for accurate assessment of IPS after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 17 Furthermore, Jin et al . 18 observed that HPS reversed in 95.8% of the liver transplant patients at 6 months; however, the prevalence of IPVD was 69.2% at 6 months, suggesting a difference between HPS and IPVD reversibility. It was also reported that cirrhosis regression induced a significant reduction in portal pressure accompanied by a normalization of systemic hemodynamics; however, there was no change in extrahepatic vascular structures.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“… 17 Furthermore, Jin et al . 18 observed that HPS reversed in 95.8% of the liver transplant patients at 6 months; however, the prevalence of IPVD was 69.2% at 6 months, suggesting a difference between HPS and IPVD reversibility. It was also reported that cirrhosis regression induced a significant reduction in portal pressure accompanied by a normalization of systemic hemodynamics; however, there was no change in extrahepatic vascular structures.…”
Section: Discussionmentioning
confidence: 86%
“…7 IPVD was also found to be associated with a higher prevalence of obstructed intrahepatic portal branches, of slowed or hepatofugal portal blood flow, and of large abdominal portosystemic shunts, 15 which was in accordance with the intra-and extrahepatic vasculature changes in cirrhosis. 17 Furthermore, Jin et al 18 observed that HPS reversed in 95.8% of the liver transplant patients at 6 months; however, the prevalence of IPVD was 69.2% at 6 months, suggesting a difference between HPS and IPVD reversibility. It was also reported that cirrhosis regression induced a significant reduction in portal pressure accompanied by a normalization of systemic hemodynamics; however, there was no change in extrahepatic vascular structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that IPVD, HPS subclinical stage, was likely to be beneficial for the early postoperative recovery of patients, which may be related to the reduction of high pulmonary artery pressure due to mild microvascular dilation. Moreover, about 35% of IPVD patients would develop into HPS over time [35], and the reversibility of IPVD was also different from HPS [36]. The above differences between HPS and IPVD may cause the difference in postoperative recovery and serum changes of cytokines.…”
Section: Discussionmentioning
confidence: 99%